2014
DOI: 10.7717/peerj.471
|View full text |Cite
|
Sign up to set email alerts
|

Is painting by elephants in zoos as enriching as we are led to believe?

Abstract: The relationship between the activity of painting and performance of stereotyped and other stress-related behaviour was investigated in four captive Asian elephants at Melbourne Zoo, Australia. The activity involved the elephant being instructed to paint on a canvas by its keeper in front of an audience. Painting by elephants in zoos is commonly believed to be a form of enrichment, but this assumption had not been based on any systematic research. If an activity is enriching we would expect stress-related beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 55 publications
0
3
0
1
Order By: Relevance
“…Cheyenne Mountain Zoo personnel trained giraffes ( Giraffa camelopardalis reticulata ) to participate in radiographs and hoof care (Dadone et al, 2016 ). Researchers have also examined the potential enriching or behavioral welfare effects of training Asian elephants ( Elephas maximus ) to paint (English et al, 2014 ), as well as training rhesus macaques ( Macaca mulatta ) to present various body parts or emit simple responses on cue (e.g., sit or stand; Baker et al, 2010 ). Finally, Zoo Atlanta researchers documented the changes in both trainer and elephant ( Loxodonta africana africana ) behaviors (e.g., frequency of trainer‐delivered cues; latency of elephant compliance) during a transition to protected contact (i.e., no human enters the elephant's habitat), positive reinforcement‐based management system (Wilson et al, 2015 ).…”
Section: Forthman and Ogden Revisitedmentioning
confidence: 99%
“…Cheyenne Mountain Zoo personnel trained giraffes ( Giraffa camelopardalis reticulata ) to participate in radiographs and hoof care (Dadone et al, 2016 ). Researchers have also examined the potential enriching or behavioral welfare effects of training Asian elephants ( Elephas maximus ) to paint (English et al, 2014 ), as well as training rhesus macaques ( Macaca mulatta ) to present various body parts or emit simple responses on cue (e.g., sit or stand; Baker et al, 2010 ). Finally, Zoo Atlanta researchers documented the changes in both trainer and elephant ( Loxodonta africana africana ) behaviors (e.g., frequency of trainer‐delivered cues; latency of elephant compliance) during a transition to protected contact (i.e., no human enters the elephant's habitat), positive reinforcement‐based management system (Wilson et al, 2015 ).…”
Section: Forthman and Ogden Revisitedmentioning
confidence: 99%
“…In contrast, there are elephants that are trained to play musical instruments [43] or draw pictures under the guidance of trainers. A study of four captive Asian elephants at the Melbourne Zoo, Australia, examined painting by elephants in zoos [53], which is believed to be a form of enrichment. However, the results indicated that the elephants gained little enrichment from the activity of painting.…”
Section: Engagement Versus Trainingmentioning
confidence: 99%
“…Хоча людина реально не створювала твір, вона визнається автором просто через свій правовий та біологічний статус. Аналогічні приклади є щодо картин, створених кроликами 22 , дельфінами 23 , білугами 24 , слонами 25 , ослами 26 та іншими тваринами.…”
unclassified